Maternal dietary patterns during pregnancy and exposure to persistent endocrine disrupting chemicals in two European birth cohorts - Kristin J. Marks (Elsevier, 2021)
Food consumption, particularly of animal-based products, is considered the most important contributor to persistent endocrine disrupting chemical (EDC) exposure. This study aims to describe the association between maternal diet during pregnancy and exposure to persistent EDCs using dietary pattern analysis. This study is based on subsamples of the Avon Longitudinal Study of Parents and Children (ALSPAC) (N=422) and the Norwegian Mother, Father, and Child Cohort Study (MoBa) (N=276) which uses data from the Medical Birth Registry of Norway (MBRN). Women in both studies completed food frequency questionnaires (FFQs) during pregnancy, from which consumption data were categorized into 38 aggregated food groups. Maternal blood samples were collected during pregnancy and concentrations of perfluoroalkyl substances (PFAS), polychlorinated biphenyls (PCBs), and organochlorine pesticides (OCPs) in serum/plasma were measured. Dietary patterns were identified using reduced rank regression, with blood EDC concentrations as response variables. Within ALSPAC, all patterns (PFAS, PCB, and OCP) were characterized by high consumption of meat, poultry, white fish, and biscuits. In MoBa, high consumption of sausages and burgers (representing processed meats), pasta, and chocolate bars characterized PCB and OCP dietary patterns, while high consumption of cheese characterized the PFAS pattern. Across both cohorts, PFAS patterns were characterized by high consumption of cheese, PCB patterns by high consumption of rice, and OCP patterns by poultry. Dietary patterns explained between 8 and 20% of the variation in serum EDC concentrations, with explained variance being the highest for PCBs in both cohorts. In conclusion, dietary patterns high in animal-based products appear to be associated with persistent EDC concentrations among pregnant women. Diet explains more variation in PCB concentrations than for other persistent EDC classes.